2014
DOI: 10.2298/psi1401113v
|View full text |Cite
|
Sign up to set email alerts
|

Materialism, narcissism and the attitide towards conspicuous consumption

Abstract: Conspicuous consumption (purchase of expensive goods and services in order to visibly demonstrate buying power) is a frequent and widely spread type of consumer behavior. Besides its economic dimension, conspicuous consumption certainly also has its - for now under studied - psychological dimension. So far, it has been reported that positive attitude towards conspicuous consumption is associated with conformity, high esteem of authority, social anxiety, Machiavellism, and ruthless self-advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Individuals seek to acquire symbols, such as brands, strongly related to what they perceive as their idealized self, and they seek ownership of high‐status goods especially when their self is under threat (Sivanathan & Pettit, ). Evidence linking materialism to conspicuous consumption (Velov, Gojkovic, & Djuric, ) suggests that conspicuous consumption may be particularly prevalent in people with an unstable self‐concept. Given their fragile self‐esteem (Morf, & Rhodewalt, ) and continuous need for confirmation of their unrealistically high self‐views (Bosson et al, ), narcissists may adopt conspicuous consumption as a self‐enhancement strategy.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Individuals seek to acquire symbols, such as brands, strongly related to what they perceive as their idealized self, and they seek ownership of high‐status goods especially when their self is under threat (Sivanathan & Pettit, ). Evidence linking materialism to conspicuous consumption (Velov, Gojkovic, & Djuric, ) suggests that conspicuous consumption may be particularly prevalent in people with an unstable self‐concept. Given their fragile self‐esteem (Morf, & Rhodewalt, ) and continuous need for confirmation of their unrealistically high self‐views (Bosson et al, ), narcissists may adopt conspicuous consumption as a self‐enhancement strategy.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The examples of representative items were the following: "People respect you more when you wear branded clothing", "Branded clothing raises confidence of people wearing it", and "Wearing branded clothing tells a good financial status". The rationales for using brand name clothes was a manifestation of conspicuous consumption among Serbian high school students, and we followed the rationale for formulating all statements in the third person given by Velov et al (2014).…”
Section: Instrumentsmentioning
confidence: 99%
“…Although far from conclusive, this psychometric evidence is congruent with the idea that conspicuous consumption goes hand in hand with other essentially antisocial behaviours. The recent paper (Velov et al, 2014) has reported predictive relationship between materialism (a strong conviction that possession and accumulation of material objects is the key for happiness and social affirmation) and ATCC. Taken together, these findings extend our understanding of psychological foundations of conspicuous consumption.…”
Section: Future Research and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the influence of social exclusion on conspicuous consumption and expanded the social exclusion theory to consumer behavior. Second, previous research has investigated the effects of antecedent variables, such as power (Rucker & Galinsky, 2009), materialism (Velov, Gojkovic, & Duric, 2014), and mating (Wang & Griskevicius, 2014), on conspicuous consumption, which contrasts with this study. We considered the effect of social exclusion as an antecedent variable on conspicuous consumption and thereby enrich conspicuous consumption research.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 72%